Kebijakan Dividen dan Profitabilitas sebagai Faktor Penentu Struktur Modal Perusahaan Manufaktur di Sektor Barang Konsumen Primer - Rambe, Aqli Nadzhari; Imsar, Imsar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study examines the influence of dividend policy and profitability on the capital structure of manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX). The research addresses inconsistent findings in prior studies regarding the relationship between these variables, drawing on the Pecking Order Theory and Trade-Off Theory as the theoretical framework. A quantitative approach was employed with purposive sampling, resulting in a sample of 32 companies observed during the 2022-2023 period. Dividend policy was measured using the Dividend Payout Ratio (DPR), profitability using Return on Equity (ROE), and capital structure as the dependent variable. Data were analyzed using multiple linear regression with SPSS version 26, preceded by classical assumption tests. The results reveal that dividend policy has a significant negative effect on capital structure, indicating that higher dividend payouts are associated with a lower proportion of debt financing. Profitability, however, does not have a significant effect on capital structure, suggesting that profit levels do not directly determine financing preferences in the sampled companies. Jointly, dividend policy and profitability significantly influence capital structure, with an adjusted R² of 19.8%, implying that other factors outside the model account for 80.2% of the variation. These findings provide practical implications for financial managers in formulating optimal financing strategies and dividend distributions, especially in the post-pandemic business environment.